Early Isolation: Racial and Economic Segregation in U.S. Public Elementary Schools - Kenty-Drane, Jessica L. (Race, Gender & Class, 2009)
The literature shows that racially and economically segregated schools diminish educational outcomes for students in non white schools with impoverished peers (Frankenberg & Lee, 2002; Mayer, 2000). To reveal which children are apt to begin their education in high minority and poor schools, this study drew on nationally representative data from the Early Childhood Longitudinal Study. Evidence documents variations in school racial and economic contexts according to children's race and social class backgrounds. Over half of Black and Hispanic first-graders attend segregated minority and poor schools while very few White first-graders do so. Additional analyses reveal that while social class is a useful predictor of educational segregation, it is less predictive for Black and Asian students than for White and Hispanic students.
Keywords: dept.soc; ⛔ No DOI found

Violence in the city of women: police and batterers in bahia, brazil - Jackson, Shirley A. (American Journal of Sociology, 2009)
Keywords: dept.soc; peer-reviewed